Analyzing the differences: U-dictionary and google translate's English-to-Indonesian speech translation - Suhartawan Budianto; Devito Andharu; Ratna Kartini (Research and Development in Education (RaDEn), 2024)
This study investigated the use of U-Dictionary and Google Translate in translating English Speech into the Indonesian language. This study aimed to test whether U-Dictionary outperforms Google Translate in translating English Speech into Indonesian. The true experimental design was applied to examine the result of the translation from U-Dictionary and Google Translate. Two raters assessed the translation result from U-Dictionary and Google Translate using a translation scoring rubric (In the "Equal Variances Assumed" section, the two-tailed significance value is 0.000, which is less than 0.05). The result showed that U-Dictionary didn’t outperform Google Translate in translating English Speech into Indonesian. On the contrary, Google Translate outperformed U-Dictionary Google Translate in translating English Speech into the Indonesian language. Here, the source language is English and the target language is Indonesian language. The result strongly suggests that Google Translate app is more effective than U-Dictionary in translating English to Indonesian in relating topics such as biography, daily life, and culture of certain community. The further research is expected to investigate the efficacy of Google Translate towards U-Dictionary in different scope of discourse like economic, politic, law, and etc. Moreover, the future research may compare among Machine Translation (MT) or among translation apps.